Exploring Fire Safety Conditions of Double Skin Facades - Aslar, Eylem Ezgi; Harputlugil, Gulsu Ulukavak (Gazi Univ, Fac Engineering Architecture, 2024)
Human health, comfort and safety are of primary importance in the built environment. Among the security measures, the most important risk is the risk of fire. For this reason, the issue of fire risk, spread and safety is considered as one of the criteria that should be considered from the building design stage. Within the scope of this study, building models with the same floor height, different plan and facade types, designed in 3D, were analyzed in the fire simulation program called PyroSim. Based on the data obtained as a result of the analyzes, the results of the temperature, smoke and flame spread at the time of fire according to the facade and plan types are presented in tables. As a result of the data obtained, it was determined that box-type systems in double-layer facades are the most problematic facade type in terms of evacuation of living creatures. In terms of smoke spread, it has been revealed that the systems that continue uninterruptedly along the facade pose a problem when the access and spread to other floors are taken into account. It is necessary to consider fire safety as a design problem. It is considered that more detailed studies should be carried out in our country on this subject, that the project should be designed by considering the simulations from the decision stage to the implementation stage of the building, and that the regulations should be developed in order to be a good guide in both the design and implementation stages.
Keywords: Fire Safety; Double Skin Facades; Fire Simulation; Fire Safety Design; Mimarlık; Termodinamik